Pituitary tumour fibroblast-derived cytokines influence tumour aggressiveness. Issue 12 (December 2019) - Marques, Pedro; Barry, Sayka; Carlsen, Eivind; Collier, David; Ronaldson, Amy; Awad, Sherine; Dorward, Neil; Grieve, Joan; Mendoza, Nigel; Muquit, Samiul; Grossman, Ashley B; Balkwill, Frances; et al.
Abstract : Tumour-associated fibroblasts (TAFs) are key elements of the tumour microenvironment, but their role in pituitary neuroendocrine tumours (PitNETs) has been little explored. We hypothesised that TAF-derived cytokines may play a role in tumour aggressiveness and that their release can be inhibited by somatostatin analogues. TAFs were isolated and cultured from 16 PitNETs (11 clinically non-functioning tumours and 5 somatotropinomas). The fibroblast secretome was assessed with a 42-plex cytokine array before and after multiligand somatostatin receptor agonist pasireotide treatment. Angiogenesis and epithelial-to-mesenchymal transition pathway assessment included CD31, E-cadherin and ZEB1 expression. GH3 cells treated with TAF- or skin fibroblast-conditioned medium were assessed for migration, invasion and cell morphology changes. PitNET TAFs secreted significant amounts of cytokines including CCL2, CCL11, VEGF-A, CCL22, IL-6, FGF-2 and IL-8. TAFs from PitNETs with cavernous sinus invasion secreted higher IL-6 levels compared to fibroblasts from non-invasive tumours ( P = 0.027). Higher CCL2 release from TAFs correlated with more capillaries ( r = 0.672, P = 0.004), and TAFs from PitNETs with a higher Ki-67 tended to secrete more CCL2 ( P = 0.058). SST1 is the predominant somatostatin receptor in TAFs, and pasireotide decreased TAF-derived IL-6 by 80% ( P < 0.001) and CCL2 by 35% ( P = 0.038). GH3 cells treated with TAF-conditioned medium showed increased migration and invasion compared to cells treated with skin fibroblast-conditioned medium, with morphological and E-cadherin and ZEB1 expression changes suggesting epithelial-to-mesenchymal transition. TAF-derived cytokines may increase PitNET aggressiveness, alter angiogenesis and induce epithelial-to-mesenchymal transition changes. Pasireotide's inhibitory effect on TAF-derived cytokines suggest that this effect may play a role in its anti-tumour effects.